Always do the parentheses first. In this case, there are two parentheses, so do the parentheses inside the other parentheses first. After that, it’s just simple addition, subtraction, and multiplication.
(69-9)= 60
(60+23)= 83
83x4= 332
Answer:
12/25 ths of the box is left.
Step-by-step explanation:
I'm assuming you mean 14% and 38%
If so then the first thing you'd do is put 38 and fourteen over 100 such as:
38/100 and 14/100. You do that because since its a percentage, its the same as the number of that percentage over 100.
Since you now have like terms, you can add them together, in which you add the two numerators (top row), but leaving the denominator (bottom row) the same, and it would give you:
52/100
What you want to do after that is simplify it. Once you simplify it, the simplified version of this is technically still the same as the non-simplified version, just easier to use.
Once you simplify it once, you will get:
26/50 and then if you simplify it again, you'll get 13/25
KEEP IN MIND that this is the amount that HAS BEEN EATEN ALREADY.
After that, you wan to subtract your part from your whole meaning you'd subtract: 25/25 - 13/25
Going back to earlier, you subtract the numerator and leave the denominator the same ONLY because they have like terms(The DENOMINATORS match)
After subtracting, you will get an answer of 12/25ths, which cannot be further simplified either.
Hope this helped!
Well, let's first solve each equation:
1.) -4x + 6 - 3x = 12 - 2x - 3x
To start, combine each like-term on each side of the equal sign (The numbers with variables in-common // the numbers alike on the same side of the equal sign):
-7x + 6 = 12 - 5x
Now, we get the two terms with variables attached to them, on the same side, so, we do the opposite of subtraction, which is, addition:
-7x + 6 = 12 - 5x
+5x +5x
_____________
-2x + 6 = 12
Next, you do the opposite of addition, which is, subtraction, and, subtract 6 from both sides:
-2x + 6 = 12
-6 -6
____________
-2x = 6
Finally, divide by -2 on each side, to find out what the value of 'x' is:
-2x = 6
÷-2 ÷-2
________
x = -3
So, the answer is not 'A.'
_________________________________________
Now, we test out the rest of the equations, the exact same way:
2.) 4x + 6 + 3x = 12 + 2x + 3x
Combine your like-terms, on each side of the equal sign:
7x + 6 = 12 + 5x
Now, get both terms, with the variable, 'x,' to the same side, and, to do that, do the opposite of addition, which is, subtraction:
7x + 6 = 12 + 5x
-5x -5x
______________
2x + 6 = 12
Next, subtract 6 from both sides:
2x + 6 = 12
-6 -6
__________
2x = 6
Finally, divide by 2, on both sides:
2x = 6
÷2 ÷2
__________
x = 3
So, the answer is 'B.'
_________________________________________
3.) 4x + 6 - 3x = 12 - 2x - 3x
Again, we combine the like-terms, on both sides of the equal sign:
x + 6 = 12 - 5x
Now, we get both terms with the variable 'x,' to the same side, and, the opposite of subtraction, is addition, so, we're going to add 5x to both sides:
x + 6 = 12 - 5x
+ 5x + 5x
______________
6x + 6 = 12
Now, we subtract 6 from each side, because, the opposite of addition, is subtraction:
6x + 6 = 12
- 6 - 6
_____________
6x = 6
Now, divide by 6, on both sides:
6x = 6
÷ 6 ÷ 6
_____________
x = 1
So, the answer is not 'C.'
_________________________________________
4.) 4x + 6 - 3x = 12x + 2x + 3x
First, we combine the like-terms:
x + 6 = 17x
Next, we get both terms, with the variable, 'x,' to the same side:
x + 6 = 17x
-x -x
_____________
6 = 16x
Now, divide by 16, on both sides:
X = 3/8
So, 'D,' is not the answer.
_______________________
The answer is, 'B.'
I hope this helps!